2012
DOI: 10.1177/1359105312465917
|View full text |Cite
|
Sign up to set email alerts
|

How Black women make sense of ‘White’ and ‘Black’ fashion magazines: A qualitative think aloud study

Abstract: This qualitative Think Aloud study explored how Black women (n=32) processed information from a White or Black fashion magazine. Comments to the 'White' magazine were characterised by rejection, being critical of the media and ambivalence, whereas they responded to the 'Black' magazine with celebration, identification and a search for depth. Transcending these themes was their self identity of being a Black woman which was brought to the fore either by a sense of exclusion (White magazine) or engagement (Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…For instance, when children compare themselves to a better-performing other, and the child contrast themselves, they may experience negative affect and feel inferior, but when they identify with a better-performing other, they may feel inspired to perform better (Dijkstra et al, 2008). In addition, research has also shown that individuals may show resilience to social comparisons when they believe the other person is not a relevant target for comparison (Ogden and Russell, 2012). Although no previous study has examined this among preadolescent boys, Anschutz et al (2012) found that 6- to 8-year-old girls showed higher body satisfaction after exposure to the thin ideal characters.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when children compare themselves to a better-performing other, and the child contrast themselves, they may experience negative affect and feel inferior, but when they identify with a better-performing other, they may feel inspired to perform better (Dijkstra et al, 2008). In addition, research has also shown that individuals may show resilience to social comparisons when they believe the other person is not a relevant target for comparison (Ogden and Russell, 2012). Although no previous study has examined this among preadolescent boys, Anschutz et al (2012) found that 6- to 8-year-old girls showed higher body satisfaction after exposure to the thin ideal characters.…”
Section: Discussionmentioning
confidence: 99%
“…Ahern et al 2011;Nasser 2009;Dittmar 2005;Clay et al 2005;Halliwell et al 2005;Halliwell and Dittmar 2004;Hargreaves and Tiggemann 2003;Harrison and Cantor 1997;Stice et al 1994). Ogden and Russell (2013) contend that this occurs because fashion models signify the 'societal ideal' (p. 1589), thus are often used as comparison figures.…”
Section: Introductionmentioning
confidence: 99%